On weakly symmetric manifolds with a type of semi-symmetric non-metric connection - YILMAZ, HÜLYA (POLISH ACAD SCIENCES INST MATHEMATICS, 2011)
The object of the present paper is to study weakly symmetric manifolds admitting a type of semi-symmetric non-metric connection.
Keywords: weakly symmetric manifold; semi-symmetric non-metric connection; special conformally flat; subprojective manifold